Prescription of statins after acute coronary syndrome; a single-centre observational study - Muhammad Muzaffar Mahmood; Nawaz, Muhammad Jabran (Journal of the Pakistan Medical Association, 2023)
There is limited information about the current use of high-intensity statins (HIS) after acute coronary syndrome (ACS) in Pakistani patients. We studied the prescription of HIS in patients admitted with ACS to Ittefaq Hospital, Lahore, Pakistan, from February 2019 to December 2019. Among the 411 patients, 221 (53.8%) patients underwent Percutaneous Coronary Intervention (PCI), 62 (15.1%) were referred for Coronary Artery Bypass Graft (CABG), and 128 (31.1%) were treated medically. Overall 408 (99.3%) patients were prescribed statins and 198 (48.2%) received HIS, with 45 (10.9%) patients receiving maximally allowed dose (Atorvastatin 80mg or Rosuvastatin 40mg). Patients treated with PCI were more likely to be prescribed HIS (73.3% vs 26.7%, p <0.001), while older patients (>75 years of age), those treated medically, and patients with severely reduced LV systolic function were significantly less likely to receive HIS (p <0.001). —Continue